REDUCING THE POLITICIZATION OF RELIGION AND DISCRIMINATION AGAINST MINORITY GROUPS AHEAD OF THE 2024 POLITICAL YEAR IN INDONESIA FROM THE PERSPECTIVE OF DIGITAL MEDIA - Ridho, Ali; Suja, Aidillah; Rifa'i, Akhmad; Masri, Muhammed Sharin Haji (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
Indonesian people have lived together in a socio-religious context in a peaceful atmosphere, full of tolerance within the framework of diversity, and prioritizing religious values. However, this peace and harmony turned into conflict, hostility, and discrimination, which was triggered by political elites using religion through identity politics and the politicization of religion to gain power in the 2019 legislative and presidential elections, which started with the fire that was ignited in the 2017 DKI Pilkada. This article uses a qualitative type virtual ethnographic method and literature review in obtaining main data derived from the search results, collection, and processing of sixty reputable national and international scientific journals, general and religious-based online news websites, to social media platforms. Digital media has become a battle arena that legitimizes narratives of the politicization of religion and identity politics which ultimately lead to social turmoil with political and religious nuances so that a series of strategies are needed by the government, religious leaders, and a plural society that are concerned about these conditions in moderating the digital world and digitalization-based cross-cultural religious literacy in the form of positive-inclusive content that is massive and has a large flow so that it exalts the political narrative of humanity which becomes the spirit of politics until finally a soothing social and digital media climate is created without any negative tendencies that become seeds of discrimination and conflict when elections come.